Exploring operational barriers encountered by community midwives when delivering services in two provinces of Pakistan: A qualitative study. Issue 1 (January 2015) - Rehman, Shafiq Ur; Ahmed, Jamil; Bahadur, Sher; Ferdoos, Amber; Shahab, Muhammad; Masud, Nazish
Abstract: Objectives: to explore barriers experienced by community midwives (CMWs) when delivering services, from their own and their managers׳ perspectives, at provincial and district level in the context of organisational factors, and to determine other factors linked with the poor performance of CMWs in the delivery of maternal, neonatal and child health (MNCH)-related services within their communities. Design: qualitative study design using in-depth interviews (IDIs) and focus group discussions (FGDs). Setting: two districts in Khyber Pakhtunkhwa and Punjab provinces in Pakistan. Participants: 41 participants were interviewed in depth; they included CMWs, lady health supervisors and managerial staff of the MNCH programme. Measurements: participants were interviewed about administrative issues including financial and policy areas, training and deployment in the community, functioning in the community, and supervision and referral for emergency cases. Findings: CMWs reported financial constraints, training needs and difficulty with building relationships in the community. They required support in terms of logistics, essential supplies, and mechanisms for referral of complicated cases to higher-level health facilities. Conclusions: CMWs working in developing countries face many challenges; starting from their training, deployment in the field and delivery of services in their respective communities. Facilitating their work and efforts through improved programming of the CMW's services can overcome these challenges. Implications for practice: the MNCH programme, provincial government and other stakeholders need to take ownership of the CMW programme and implement it comprehensively. Long-term adequate resource allocation is needed to sustain the programme so that improvements in maternal and child health are visible.